When God lost her tongue - Hobson, Janell, 1973- author.
1 online resource
Keywords: "When God Lost Her Tongue seeks to explore historical consciousness as captured through the Black feminist imagination that re-centers the perspectives of Black women in the African Diaspora, and revisits how Black women's transatlantic histories are re-imagined and politicized in our contemporary moment. Connecting select historical case studies - from the Caribbean and Latin America, the African continent, North America, and Europe - while also examining the retelling of these histories in the work of present-day writers and artists, Janell Hobson utilizes a Black feminist lens to rescue the narratives of African-descended women, which have either been marginalized, erased, forgotten, and/or mis-remembered. They are often invoked, but sometimes we forget their names. African goddesses crossing the Atlantic with captive Africans. Women leaders igniting the Haitian revolution. Unnamed Black women in European paintings. African women on different sides of the "door of no return" during the era of the transatlantic slave trade. Even ubiquitous "Black queens" heralded and signified in a Beyoncé music video or a Janelle Monáe lyric. And then there are those whose names we will never forget, like the iconic Harriet Tubman. This critical interdisciplinary intervention will be key reading for students and researchers studying African American Women, Black Feminisms, Feminist Methodologies, Africana Studies, Women and Gender Studies"--